2019
DOI: 10.1097/xce.0000000000000169
|View full text |Cite
|
Sign up to set email alerts
|

The early detection of atherosclerosis in type 1 diabetes: why, how and what to do about it

Abstract: The major cause of morbidity and often premature mortality in people with type I diabetes (T1D) is cardiovascular disease owing to accelerated atherosclerosis. We review publications relating to the rationale behind, and clinical tests for, detecting and treating early atherosclerosis in people with T1D. Currently available tools for atherosclerosis assessment include risk equations using vascular risk factors, arterial intima–media thickness, the ankle–brachial index, coronary artery calcification and angiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 177 publications
0
15
0
Order By: Relevance
“…The risk of vascular complications development in type 1 diabetes in children, greater with worse metabolic control, is also exacerbated by lipid disorders [ 58 ]. The described results are in line with many formerly published research works considering youth diabetic cases [ 33 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of vascular complications development in type 1 diabetes in children, greater with worse metabolic control, is also exacerbated by lipid disorders [ 58 ]. The described results are in line with many formerly published research works considering youth diabetic cases [ 33 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the development of cardiovascular disease, early intervention is necessary. A randomized, controlled, double-blind, 1-year study that involved 90 people demonstrated that metformin at a dosage of 1 g twice a day is capable of improving SMCs and HbA1c function in children with T1DM and reducing insulin doses [ 69 ].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Endothelial dysfunction defined as an abnormal vascular response to endothelium-dependent vasodilators can be assessed by non-invasive ultrasound methods, while endothelial activation is detected by testing the concentration of substances produced by the endothelium in the blood serum. Jenkins et al draws attention to the need to improve diagnostic methods for measuring arterial intima-media thickness, coronary artery calcification and angiography, and other methods like intravascular ultrasound and optical coherence tomography [34]. The same authors also emphasize the need to improve novel clinical, biochemical and molecular tests; vascular MRI and molecular imaging.…”
Section: Diagnosticsmentioning
confidence: 99%